PENGARUH REGULASI EMOSI DAN INTERAKSI SOSIAL TERHADAP HARGA DIRI (SELF-ESTEEM) SISWA SMA Dr. SOETOMO SURABAYA - Cindy Asli Pravesti; Ariella Candraningtyas Sari (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
The context of this study focuses on the influence of emotional regulation and social interaction on students' self-esteem, which is an important part of adolescent development. In today's modern era, adolescents are often faced with various emotional and social challenges that can affect their views of themselves. This study aims to explore how students' ability to manage emotions and the quality of social interactions they experience can play a role in forming positive self-esteem. This type of research is quantitative research with the research design used is a correlational design. The research data were collected through three different mesasurement scales, with a total sample of 162 students. Data analysis was conducted using descriptive methods to provide an overview, as well as multiple regression analysis to test the relationship between variables. Prior to the regression analysis, a series of prerequisite tests were conducted, including normality tests, heteroscedasticity tests, and multicollinearity tests, to ensure that the data met the required assumptions. The results of the study showed a positive and significant influence between emotional regulation and social interaction on self-esteem, which means that both variables contribute to self-esteem. Emotional regulation and social interaction have an influence of 45.9% on students' self-esteem.